2017
DOI: 10.4322/0104-4931.ctoao0820
|View full text |Cite
|
Sign up to set email alerts
|

O Brincar Para O Desenvolvimento Do Esquema Corporal, Orientação Espacial E Temporal: Análise De Uma Intervenção

Abstract: Resumo: Introdução: A infância é uma fase significativa do desenvolvimento humano, na qual se desenvolvem várias aptidões, ocorrendo evoluções na aprendizagem. O ato de brincar é uma atividade do cotidiano das crianças e aperfeiçoa as habilidades cognitivas, sociais, emocionais e psicomotoras. Objetivo: Avaliar os resultados de uma intervenção para uma criança com atraso no desenvolvimento do esquema corporal, da orientação espacial e da orientação temporal. Método: Este estudo adotou o design quase-experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
6
Order By: Relevance
“…Para Campos et al (2017), a brincadeira é uma atividade social e cultural que pressupõe um aprendizado. Mas, para que esse aprendizado ocorra, a criança precisa experimentar alguma coisa para que tenha a habilidade de pensar sobre ela.…”
Section: Discussionunclassified
“…Para Campos et al (2017), a brincadeira é uma atividade social e cultural que pressupõe um aprendizado. Mas, para que esse aprendizado ocorra, a criança precisa experimentar alguma coisa para que tenha a habilidade de pensar sobre ela.…”
Section: Discussionunclassified
“…In both studies, the children attending private institutions obtained better scores, emphasizing better attention skills and motor stimulation in those environments. In a study by Campos et al [34], the positive effect of therapeutic intervention was demonstrated through plays and ludic activities on the body and spatial perception and temporal organization in a 4-year-old child.…”
Section: Regarding Motor Quotients In Each Domain and General Motor Qmentioning
confidence: 98%
“…The temporal organization refers to the ability to discriminate a succession of events and duration of intervals (notions of rhythm, beat and time). Body and spatial perceptions are essential requirements to a good motor and school performance [34], and reading, writing and calculation disabilities might be directly related to perceptual-motor disorders [27]. Recently, a systematic review involving children aged between 4 and 16 years with typical development, pointed out that better motor abilities were commonly associated with better performance in cognitive tasks [35].…”
Section: Regarding Motor Quotients In Each Domain and General Motor Qmentioning
confidence: 99%
“…Enquanto aspecto fundamental do cotidiano infantil, o brincar é um espaço de intervenção privilegiado na clínica da Terapia Ocupacional e da Fonoaudiologia com bebês, pois está presente na avaliação bem como na terapia de crianças que apresentam alguma alteração no desenvolvimento (CAMPOS et al, 2017). O brincar é considerado uma ação livre e subjetiva na criança, permeada por prazer e curiosidade (SANT'ANNA; BLASCOVI-ASSIS; MAGALHÃES, 2008).…”
Section: Introductionunclassified